Arrhythmias in primary hyperparathyroidism evaluated by exercise test. (22nd December 2012) - Pepe, Jessica; Curione, Mario; Morelli, Sergio; Colotto, Marco; Varrenti, Marisa; Castro, Claudia; D'Angelo, Antonella; Cipriani, Cristiana; Piemonte, Sara; Romagnoli, Elisabetta; Minisola, Salvatore
Abstract Background Hypercalcemia induces arrhythmias and shortening of QT. The aim of this study was to investigate risk factors for occurrence of arrhythmias in patients with primary hyperparathyroidism (PHPT) during bicycle ergometer exercise test (ET). Methods Thirty PHPT postmenopausal women (mean age, 60·9 ± 8·0 years) and 30, sex and age‐matched, controls underwent ET, echocardiogram and mineral metabolism biochemical evaluation. The following stages were considered during ET: rest, peak exercise, recovery (early recovery, 2 and 10 min after peak exercise). QT was corrected with Bazett's formula (QTc). Results Compared with controls, PHPT patients showed an increased occurrence of ventricular premature beats (VPBs) during ET (26·6% vs. 6·6%, P = 0·03). Being affected by PHPT predicted the onset of VPBs at peak exercise (P = 0·04) and recovery (P = 0·03), as shown by logistic regression analysis. In PHPT patients, serum calcium level was a predictor of VPBs at peak exercise (P = 0·05). QTc in patients with PHPT was in the normal range. Serum calcium level showed a negative correlation with QTc (P = 0·01) in whole sample. Compared with controls, PHTP patients had QTc significantly shorter for every stage of ET, except at peak exercise. Physiological reduction of QTc interval from rest to peak exercise was not seen in patients with PHPT, QTc at rest being the only predictor of QTc in every stage, as shown by multivariate regression analysis. Conclusions In patients with PHPT, an increased occurrence of VPBs and a different QTc adaptation during ET were observed and may represent risk factors for major arrhythmias.